ULTRASOUND CRITERIA OF EARLY DIAGNOSTICS OF OVARIAN CARCINOMA - L. A. Ashrafyan; N. A. Babaeva; I. B. Antonova; S. V. Ivashina; A. V. Lyustik; O. I. Aleshikova; E. V. Gerfanova; А. А. Dobrenko (Опухоли женской репродуктивной системы)
Introduction. Ovarian cancer (OC) in Russia is ranked the seventh within the structure of general cancer diseases and the third within the gynecological tumors, due to such reasons the problem of early diagnostics is still actual. New technologies, such as color Doppler ultrasonography,3D power Doppler ultrasonography contribute to increasing of opportunities of ultrasound analysis to detect any malignancy signs.Materials and methods. The paper sets out the results of comprehensive ultrasound study of 68 patients with morphologically verified OC at stages IА–В, IIА–В. The control group was made of 100 female patients with morphologically verified ovarian tumors (serosal cystadenomas, thecomas, fibromas). A complex of the following ultrasound methods was used during the study: 2D and 3D ultrasonography in B mode, in color Doppler and power mapping mode, 3D angiography, spectrum Doppler imaging.Results. Maximum size of tumor varied within a range between 37 and 300 mm (108 ± 61.2 mm). It worth noting that no direct dependence between the size of neoplasm and process phase was established. When assessing the echostructure, all ovarian tumors were divided into 3 structure types: cystic type (57.8 % of cases), cystic and solid type (33.3 % of cases), solid type (8.9 % of cases). The conducted analysis of types of small pelvis neoplasm echostructures enabled to evolve the sonographic types of ovarian tumors, more or less associated with the malignant transformation. The most relevanl Doppler ultrasonography exponents characteristic for benignant and malignant processes: resistance index in benignant tumors was 0.56, at OC – 0.32 (р < 0.001); average arterial blood velocity in benignant tumors – 7.8 cm/s, at OC – 20.1 cm/s (р < 0.001); average maximum venous flow velocity in benignant tumors – 3.2 cm/s, at OC – 9.3 cm/s (р < 0.001).Conclusion. Therefore modern ultrasonography can detect and differentiate rather efficiently the localized variants of OC, provided that the main part of diagnosis is formed in mode of color and power Doppler mapping, which shall be taken into consideration during the primary diagnostics of OC.